An observational assessment of the safety of mass drug administration for trachoma in Ethiopian children. (1st February 2022) - Ciciriello, Allan M; Addiss, David G; Teferi, Tesfaye; Emerson, Paul M; Hooper, P J; Seid, Mohammed; Tadesse, Girma; Seife, Fikre; Sormolo, Mohammed-Aman Jemal; Kebede, Fikreab; Kiflu, Genet; West, Sheila K; et al.
Abstract: Background: The International Trachoma Initiative (ITI) provides azithromycin for mass drug administration (MDA) to eliminate trachoma as a public health problem. Azithromycin is given as tablets for adults and powder for oral suspension (POS) is recommended for children aged <7 y, children <120 cm in height (regardless of age) or anyone who reports difficulty in swallowing tablets. An observational assessment of MDA for trachoma was conducted to determine the frequency with which children aged 6 mo through 14 y received the recommended dose and form of azithromycin according to current dosing guidelines and to assess risk factors for choking and adverse swallowing events (ASEs). Methods: MDA was observed in three regions of Ethiopia and data were collected on azithromycin administration and ASEs. Results: A total of 6477 azithromycin administrations were observed; 97.9% of children received the exact recommended dose. Of children aged 6 mo to <7 y or <120 cm in height, 99.6% received POS. One child experienced choking and 132 (2%) experienced ≥1 ASEs. Factors significantly associated with ASEs included age 6–11 mo or 1–6 y, non-calm demeanor and requiring coaxing prior to drug administration. Conclusions: There is a high level of adherence to the revised azithromycin dosing guidelines and low incidence of choking and ASEs.